AN INTEGRATION OF SOFTWARE TESTING TOOLS AND TECHNIQUES WITH VISUAL GUI INTERFACE IN INDUSTRIAL PRACTICE - Yadu, Priyanka; Narain, Bhawana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Software testing with visual Graphical User Interface (GUI) techniques is being done while maintaining a high level of accuracy with the ever-growing demand for speedier delivery of high-quality software, often known as "Quality at Speed". The use of relevant testing methodology(s) and the choice of suitable test automation tools and frameworks are two key components for a successful and efficient software testing project. A mix of numerous distinct testing processes is often necessary when testing software to make sure it is up to par; the use of a single testing method will not be sufficient. Similar to the previous point, finding the right tool combination for automated testing is difficult because no single tool can meet all of the needs. The first step in performing successful and efficient software testing is to familiarize industrial professionals with the various testing techniques, tools, and frameworks. An in-depth examination of the various test automation tools and frameworks is provided in this paper. An explanation of the various frameworks for test automation was delivered after an overview of automated testing and the categories it fits under. Finally, a brief summary of a few of the most popular automation solutions was provided, along with a comparison of those programs.